Effect of full arch two scanning techniques on the accuracy of overdenture conventional and CAD/CAM Co-Cr bars - Ali Alenezi; Mohammed Yehya; Mohamed Alkhodary (Elsevier, 2022)
Purpose: This work evaluates the internal and marginal adaptation of implant-assisted overdenture cobalt-chromium (Co-Cr) bars manufactured using conventional as well as CAD/CAM subtractive and selective laser melting (SLM) utilizing two scanning techniques. Methods: An edentulous study model containing four dental implants placed at teeth sites 36, 33, 43, and 46 was used. The study cast was scanned and compared to the virtual casts developed from two scanning techniques, straight and zigzag motion, using the in silico superimposition process. Then, conventional techniques were used to produce full-arch bars that were compared to the bars fabricated using the two scanning techniques and CAD/CAM subtractive and additive techniques. Results: The conventional impression and casting techniques had the smallest marginal gap among the groups (P-value < 0.05). The CAD/CAM subtractive milling techniques in groups II and III had significantly smaller marginal gaps than SLM technique used in groups IV and V (P-value < 0.05). The analysis of the internal gap within each group showed statistically significant differences between different implant sites in all groups (P-value < 0.001), except when using the conventional impression and casting techniques in group I (P-value = 0.20). Conclusion: The conventional impression and fabrication techniques were better than the digital impression and CAD/CAM subtractive and additive techniques for the fabrication of full-arch bars. However, both straight and zigzag scanning techniques and the CAD/CAM subtractive technique had marginal and internal gaps that were within clinically accepted ranges, and the SLM was found to be unsuitable for long-span framework fabrication with either scanning technique used.